Clinical outcomes in stage III non-small cell lung cancer patients treated with durvalumab after sequential or concurrent platinum-based chemoradiotherapy - Vrankar, Martina (Radiology and oncology (Ljubljana), 2021)
Chemoradiotherapy (ChT-RT) followed by 12-month durvalumab is the new standard treatment for unresectable stage III non-small cell lung cancer. Survival data for patients from everyday routine clinical practice is scarce, as well as potential impact on treatment efficacy of sequential or concomitant chemotherapy and the us-age of gemcitabine.Patients and methods. We retrospectively analysed unresectable stage III NSCLC patients who were treated with durvalumab after radical concurrent or sequential chemotherapy (ChT) from December 2017 and completed treat-ment until December 2020. We assessed progression free survival (PFS), overall survival (OS) and toxicity regarding baseline characteristic of patients.Results. Eighty-five patients with median age of 63 years of which 70.6% were male, 56.5% in stage IIIB and 58.8% with squamous cell carcinoma, were included in the analysis. Thirty-one patients received sequential ChT only, 51 patients received induction and concurrent ChT and 3 patients received concurrent ChT only. Seventy-nine patients (92.9%) received gemcitabine and cisplatin as induction chemotherapy and switched to etoposide and cisplatin during con-current treatment with radiotherapy (RT). Patients started durvalumab after a median of 57 days (range 12–99 days) from the end of the RT and were treated with the median of 10.8 (range 0.5–12 months) months. Forty-one patients (48.2%) completed treatment with planned 12-month therapy, 25 patients (29.4%) completed treatment early due to the toxicity and 16 patients (18.8%) due to the disease progression. Median PFS was 22.0 months, 12- and estimated 24-month PFS were 71% (95% CI: 61.2–80.8%) and 45.8% (95% CI: 32.7–58.9%). With the median follow-up time of 23 months (range 2–35 months), median OS has not been reached. Twelve- and estimated 24-month OS were 86.7% (95% CI: 79.5–93.9%) and 68.6% (95% CI: 57.2–79.9%).Conclusions. Our survival data are comparable with published research as well as with recently published real-world reports. Additionally, the regimen with gemcitabine and platinum-based chemotherapy as induction treatment was efficient and well tolerated.
Keywords: acute toxicity; chemoradiotherapy; durvalumab; non-small cell lung cancer; stage III